PENGARUH SENAM AEROBIK LOW IMPACT TERHADAP KADAR GULA DARAH PADA WANITA PENYANDANG DIABETES MELITUS - laksana, anggun syah putri (Jurnal Kesehatan Olahraga, 2019)
ABSTRACT Diabetes mellitus, experienced by many adults aged over 40 years, often occurs in someone with obesity. Most are women. How to maintain blood sugar stability and complications of diabetes mellitus by giving exercises Low Impact Aerobics. The purpose of this study was to determine the effect of exercises Low Impact Aerobics on blood sugar levels in women with diabetes mellitus in Prolanis Cempaka Husada participants in Bojonegoro. This research uses research Quasi Experiments approaches Pre-test Post-test. The sample research was 12 women with diabetes mellitus in Prolanis Cempaka Husada participants in Bojonegoro. Gymnastics Aerobic is done continuously for 60 minutes, 3 times a week for 6 weeks. The results of the test Descriptive Statistics obtained average blood sugar levels Pre-Test 197.42 mg/dl, the average blood sugar levels Post-Test 140.50 mg /dl and the results of T test (paired samples) this study showed p value = 0.00 <0.05. So it can be concluded that exercises Low Impact Aerobics have an effect on decreasing the blood sugar levels of women with diabetes mellitus. Keywords: Diabetes Mellitus, Blood Sugar Levels, Low Impact Aerobics.